PENYEBAB KETERLAMBATAN PENGIRIMAN BARANG IMPOR PADA CUSTOMER - okin ringan purba; jeniffer wanda (Institut Transportasi dan Logistik Trisakti, 2014)
There are four problems found when delivering the imported goods and being delayed. First, the manpower problem which is related to the number of employees with a percentage of 71.88%. The second problem is machines (technology and computer systems) with a percentage of 53.33 %. The third is methods which are forecasting with a percentage of 56.25 % and administration (78.13%). The last one is motivation which is known as welfare with 53.13 % of percentage.